Representation of Language Functions in Habiburrahman El Shirazy’s Novel Pudarnya Pesona Cleopatra - Bela Audy Hayati; Gazali; Pratama Bayu Santosa; Agustan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to outline the language roles found in the novel "Pudarnya Pesona Cleopatra" by Habiburrahman El Shirazy. The study utilized qualitative descriptive research employing content analysis methods. The researcher focused this study by using Roman Jakobson's theory of language functions, which proposes that language functions consist of six functions: referential, emotive, poetic, phatic, conative, and metalingual functions. The data source for this study was obtained from the novel Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy, the 27th edition published by Republika Publisher in 2019. Data collection in this study used reading and note-taking techniques. The results of this study indicate that there are six language functions in the novel Pudarnya Pesona Cleopatra by Habiburrahman El Shirazy. The total data included in these six functions amounted to 212 data points. The dominant language functions are the emotive function with 87 data points and the referential function with 77 data points.